An Analysis of Poverty Using the System-GMM Approach: Evidence from Dynamic Panel Data in East Nusa Tenggara Province - Pandu, Marvin Jecson (Universitas Islam Negeri Alauddin Makassar, 2025)
This study focuses on the application of the System-Generalized Method of Moments (System-GMM) statistical approach to analyze the determinants of poverty in 22 districts/municipalities in East Nusa Tenggara Province (NTT) over the period 2015–2019. The GMM method is employed to address issues of endogeneity, heterogeneity, and data persistence that are commonly encountered in regional socio-economic studies. By utilizing internal instruments, this approach enables more valid and robust parameter estimation. The panel data, obtained from the Central Bureau of Statistics, includes variables such as the Human Development Index (HDI), Open Unemployment Rate (OUR), and electrification ratio. The estimation results show that HDI has a negative and significant effect on poverty, with short-term and long-term elasticities of -0.984 and -2.244, respectively. The OUR has a positive and significant effect on poverty, with elasticities of +0.016 (short-term) and +0.036 (long-term), while the electrification ratio also shows a negative and significant effect, with elasticities of -0.035 and -0.081. These findings affirm that the application of the System-GMM method provides a more accurate depiction of the causal relationships among the determinants and supports evidence-based policymaking for poverty alleviation in structurally challenged regions such as NTT.